Pollen from the Deep-Sea: A Breakthrough in the Mystery of the Ice Ages - Sánchez Goñi, María F.; Desprat, Stéphanie; Fletcher, William J.; Morales-Molino, César; Naughton, Filipa; Oliveira, Dulce; Urrego, Dunia H.; Zorzi, Coralie (Frontiers in Plant Science, 2018)
Pollen from deep-sea sedimentary sequences provides an integrated regional reconstruction of vegetation and climate (temperature, precipitation and seasonality) on the adjacent continent. More importantly, the direct correlation of pollen, marine and ice indicators allows comparison of the atmospheric climatic changes that have affected the continent with the response of the Earth’s other reservoirs, i.e. the oceans and cryosphere, without any chronological uncertainty. The study of long continuous pollen records from the European margin has revealed a changing and complex interplay between European climate, North Atlantic sea surface temperatures, ice growth and decay, and high- and low-latitude forcing at orbital and millennial timescales. These records have shown that the amplitude of the last five terrestrial interglacials was similar above 40°N, while below 40°N their magnitude differed due to precession-modulated changes in seasonality and, particularly, winter precipitation. These records also showed that vegetation response was in dynamic equilibrium with rapid climate changes such as the Dangaard-Oeschger (D-O) cycles and Heinrich events, similar in magnitude and velocity to the ongoing global warming. However, the magnitude of the millennial-scale warming events of the last glacial period was regionally-specific. Precession seems to have imprinted regions below 40°N while obliquity, which controls average annual temperature, probably mediated the impact of D-O warming events above 40°N. A decoupling between high- and low-latitude climate was also observed within last glacial warm (Greenland interstadials) and cold phases (Greenland stadials). The synchronous response of western European vegetation/climate and eastern North Atlantic sea surface temperatures to D-O cycles was not a pervasive feature throughout the Quaternary. During periods of ice growth such as MIS 5a/4, MIS 11c/b and MIS 19c/b, repeated millennial-scale cold-air/warm-sea decoupling events occurred on the European margin superimposed to a long-term air-sea decoupling trend. Strong air-sea thermal contrasts promoted the production of water vapor that was then transported northwards by the westerlies and fed ice sheets. This interaction between long-term and shorter time-scale climatic variability may have amplified insolation decreases and thus explain the Ice Ages. This hypothesis should be tested by the integration of stochastic processes in Earth models of intermediate complexity.